Simulation and Development of Biomimetic Electrospun PCL Nanofibrous Tympanic Membrane Implants. Issue 1 (25th January 2021) - Chen, Zhaoyu; Benecke, Lukas; Kempert, Philipp; Stoppe, Thomas; Bornitz, Matthias; Neudert, Marcus; Aibibu, Dilbar; Cherif, Chokri; Zahnert, Thomas
Abstract: Electrospun membranes have a great potential in myringoplasty, as the special microstructure of fibers could be comparable to the fiber structure of the tympanic membrane (TM), thus, making it an potential implant for tympanic membrane reconstruction. In this work, the microscale parameters of the fiber structure were studied in a numerical homogenization procedure. The aim of the investigations was to obtain an implant that has a compromise between acoustic and mechanical properties and which at macroscale is comparable with the human TM. The numerical results were verified with experiments on first samples.